Isolation and Identification of Heavy Metal Tolerant Bacteria from Tannery Effluents (Bangladesh Journal of Microbiology, 2016)
The aim and objective of the study was to isolate and characterize heavy metal tolerant microorganisms from tannery effluents. Six effluent samples were collected aseptically and their physical and chemical parameters were determined. A total of 40 bacterial colonies were isolated from these effluent samples. Among them, six bacterial isolates were characterized provisionally as Alcaligenes aquamarinus, Bacillus coagulans, Bacillus firmus, Enterobacter cloacae, Pseudomonas alcaligens and Pseudomonas mendocina based on morphological, cultural and biochemical characteristics. The survibality and tolerance to heavy metals (Cr and Cu) of these isolates were examined. All the isolates were found to grow at high concentration of CuSO4 (95ppm/ml) and varying degrees of chromium (K2Cr2O7). The highest tolerance was shown by Alcaligenes aquamarinus. These heavy metal tolerant organisms could be potential agents for bioremediation of heavy metals polluted environment.Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 23-26